2014
DOI: 10.1371/journal.pone.0095354
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Risk and Mortality of Edoxaban: A Pooled Meta-Analysis of Randomized Controlled Trials

Abstract: Objective(s)Edoxaban, a factor Xa inhibitor, is a new oral anticoagulant that has been developed as an alternative to vitamin K antagonists. However, its safety remains unexplored.MethodsMedline, Embase and Web of Science were searched to March 8, 2014 for prospective, randomized controlled trials (RCTs) that assessed the safety profile of edoxaban with warfarin. Safety outcomes examined included bleeding risk and mortality.ResultsFive trials including 31,262 patients that met the inclusion criteria were poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…The RRs of edoxaban at 30, 60, or 120 mg/day gradually increased with regard to bleeding; at the 120 mg/day dose, the bleeding risk was higher than warfarin. 30 This was similar to our results. We also found a significant decrease in allcause mortality, major bleeding, CRNM bleeding, and minor bleeding when edoxaban was compared with warfarin, although they were not significantly different in terms of all bleeding categories.…”
Section: Discussionsupporting
confidence: 93%
“…The RRs of edoxaban at 30, 60, or 120 mg/day gradually increased with regard to bleeding; at the 120 mg/day dose, the bleeding risk was higher than warfarin. 30 This was similar to our results. We also found a significant decrease in allcause mortality, major bleeding, CRNM bleeding, and minor bleeding when edoxaban was compared with warfarin, although they were not significantly different in terms of all bleeding categories.…”
Section: Discussionsupporting
confidence: 93%
“…Major gastrointestinal bleeding was shown to occur more frequently with 60 mg edoxaban than well‐managed warfarin in 21 105 patients with NVAF . On the other hand, a subgroup analysis of pooled meta‐analysis of randomized controlled trials (RCTs) with 31 262 patients indicated that the rates of bleeding with edoxaban 30, 60 or 120 mg/d were significantly lower than those for warfarin . Because the results of these studies are conflicting, bleeding safety remains to be explored.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Because the results of these studies are conflicting, bleeding safety remains to be explored. Moreover, the previous studies analysed the data from RCTs, which may not have included enough patients with bleeding risks such as renal insufficiency and low body weight . Therefore, an individualized approach should be adopted in some patients to decide the appropriate anticoagulation regimen after weighing the overall risks and benefits of therapy .…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 2 more Smart Citations